Employer understanding of Work-Integrated Learning and the challenges of engaging in work placement opportunities - Jackson, D.; Rowbottom, D.; Ferns, Sonia; McLaren, D. (Carfax Publishing, 2016)
This study examines employer understanding of Work-Integrated Learning (WIL), reasons for participation and the challenges and barriers posed during the WIL process. This is important given the drive to grow WIL, augmented by the National Strategy for WIL, and the significant benefits it holds in preparing students for their transition to employment. The study was undertaken by the four publicly funded Western Australian universities, in partnership with the Chamber of Commerce and Industry of Western Australia, and is focused on work placements among business students. Findings indicate employers had very little understanding of WIL offerings at the four Business Schools. While employers generally believed that student work placements are useful for their industry sectors, a number of issues impacted on their engagement in WIL. These included identifying suitable projects and tasks for students to complete; sourcing suitable students; concerns with student performance and capacity to mentor/supervise. A combination of quantitative and qualitative research tools were used with data gathered by an employer survey (N?=?112) and focus group sessions (N?=?17). The study recommends a number of ways to alleviate barriers and challenges to improve the WIL experience for all stakeholders and ensure the sustained growth of WIL in the higher education sector. © 2016 Informa UK Limited, trading as Taylor & Francis Group.